Regulation Disclosure and Dynamics Cost of Capital: An Overview Literature About Effect Externalities in Financial Markets - Evlin Candra Rita; Andrew Subhana (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This qualitative literature review examines the interplay between disclosure regulation, capital costs, and externalities in financial markets. It highlights how regulatory frameworks aimed at increasing transparency can significantly affect companies' capital costs and market dynamics. Through an extensive analysis of existing literature, this study reveals that while enhanced disclosure can reduce information asymmetry and lower capital costs, it can also generate negative externalities for non-regulated firms. The review compares findings from eight previous studies, illustrating the complexities of information dissemination and its repercussions on both regulated and unregulated entities. Furthermore, it underscores the importance of designing comprehensive regulatory policies that not only promote transparency but also consider the broader market implications. The findings indicate that selective disclosure regulations may inadvertently create imbalances in the market, leading to increased overall capital costs. This research contributes to the ongoing discourse on financial regulation by providing insights into the effects of disclosure practices on capital costs and market efficiency